Climate change and the future distribution of palsa mires : ensemble modelling, probabilities and uncertainties - Fronzek, Stefan (Suomen ympäristökeskus, 2013)
Palsas are mounds with a permafrost core covered by peat. They occur in subarctic palsa mires, which are ecologically valuable mire complexes located at the outer margin of the permafrost zone. Palsas are expected to undergo rapid changes under global warming. This study presents an assessment of the potential impacts of climate change on the spatial distribution of palsa mires in northern Fennoscandia during the 21st century. A large ensemble of statistical climate envelope models was developed, each model defining the relationship between palsa occurrences and a set of temperature- and precipitation-based indicators. The models were used to project areas suitable for palsas in the future. The sensitivity of these models to changes in air temperature and precipitation was analysed to construct impact response surfaces. These were used to assess the behaviour of models when extrapolated into changed climate conditions, so that new criteria, in addition to conventional model evaluation statistics, could be deﬁned for determining model reliability. A special focus has been on comparing alternative methods of representing future climate, applying these with impact models and quantifying different sources of uncertainty in the assessment. Climate change projections were constructed from output of coupled atmosphere-ocean general circulation models as well as finer resolution regional climate models and uncertainties in applying these with impact models were explored. New methods were developed to translate probabilistic climate change projections to probabilistic estimates of impacts on palsas. In addition to future climate, structural differences in impact models appeared to be a major source of uncertainty. However, using the model judged most reliable according to the new criteria, results indicated that the area with suitable climatic conditions for palsas can be expected to shrink considerably during the 21st century, disappearing entirely for an increase in mean annual air temperature of 4°C relative to the ...